Pornography: A critical analysis based on ethical and social perspective. - Poologanathan, P. (University of Jaffna, 2016)
Pornography is one of the major social-ethical problems in the current society. Pornography refers to writings or movies on all kinds of sexual activities out site the bound of marriage. It has emerged as a serious threat to the dignity of human sexuality and its divine purpose, challenging the very nature of man and women and representing the perversion of the mind in contemporary age. It has tainted the sanctity and purity of sex, promoted degradation of human hood and advanced the commercialization of sex. Despite its explicitly harmful effects, pornography has been defended as of potentially therapeutic value of overcoming sexual problems such as frigidity and impotence. As a seriously social-ethical problems in current society, this essay try to offers that a systematic analysis of the merits, demerits and defenses of pornography based on social and ethical perspective and suggest possible solution to this problem. For this study, critical and descriptive methods are used and also data are collected from secondary sources.
Keywords: Deontological ethics; Ethics; Pornography; Sexual problem; Violence